Familial colorectal cancer. Issue 5 (May 2015) - Lung, M. S.; Trainer, A. H.; Campbell, I.; Lipton, L.
Abstract Identifying individuals with a genetic predisposition to developing familial colorectal cancer (CRC) is crucial to the management of the affected individual and their family. In order to do so, the physician requires an understanding of the different gene mutations and clinical manifestations of familial CRC. This review summarises the genetics, clinical manifestations and management of the known familial CRC syndromes, specifically Lynch syndrome, familial adenomatous polyposis, MUTYH‐associated neoplasia, juvenile polyposis syndrome and Peutz–Jeghers syndrome. An individual suspected of having a familial CRC with an underlying genetic predisposition should be referred to a familial cancer centre to enable pre‐test counselling and appropriate follow up.